Influence of rosemary, andiroba and copaiba essential oils on different stages of the biological cycle of the tick Rhipicephalus microplus in vitro - Volpato A.* (2015)
© 2015 Taylor & Francis.The aim of this study was to verify in vitro the influence of rosemary, andiroba, and copaiba essential oils on different stages of the cattle tick Rhipicephalus microplus. Female ticks were collected from naturally infected cows and treated in vitro with these essential oils at concentrations of 5% and 10%. All tests were performed in triplicate using positive (amitraz 10%) and negative (untreated) controls. It was possible to observe that rosemary, andiroba, and copaiba essential oils inhibited female reproduction at concentrations of 5% (45.0%, 77.5%, and 71.6%, respectively) and 10% (55.7%, 92.0,% and 86.7%, respectively) compared with amitraz (72.9%). Additionally, andiroba (10%) and copaiba (5% and 10%) oil solutions also had an acaricidal effect (100%), similarly to the positive control. The andiroba and copaiba oils showed an ovicidal effect, which effected hatchability. Rosemary oil showed neither acaricidal nor ovicidal effect. Therefore, based on these results, we were able to show that all oils and concentrations tested may affect tick reproduction by inhibiting tick oviposition and hatchability. In addition, andiroba and copaiba oils exhibited ovicidal and acaricidal effects.